THE RELATIONSHIP BETWEEN THE TEACHING STYLE OF SWIMMING COACHES AND THEIR ATHLETES’ MOTIVATION FOR SPORT - Razmaite, Danguole; Grajauskas, Lauras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The paper presents a research dealing with one of the most relevant problems in sports education science, the coach’s influence on young athletes’ motivation. The aim of the research is to investigate the correlations between manifestation of the teaching style applied by coaches and motivation of their athletes for sport. The research raises a hypothesis that the teaching styles applied by coaches may be related to the motivation for sport in the athletes being trained. The research is based on the provisions of reproductive and productive teaching methods as well as the self-determination theory. The research involved 14–18-year-old swimmers and their coaches. Two questionnaires have been employed: description of the teaching style (Curtner-Smith et al., 2001; Hein et al., 2012) and sport motivation scale (SMS–II; Pelletier et al., 2013). Referring to the responses in relation to manifestation of the teaching style, the coaches have been divided into three groups. The one factor analysis of variance (ANOVA) was applied to test the research hypothesis. The research hypothesis was proven only partly. It was found that application of different teaching styles may have had effect on young athletes’ external motivation only. It can be substantiated that the teaching style employed by swimming coaches and related both reproductive and reproductive teaching methods have no significant effect on young athletes’ intrinsic motivation for sport in the coaching practise.